Ischemia-modified albumin in migraine patients during interictal period - Michalak, Slawomir; Osztynowicz, Krystyna; Płóciniczak, Alicja; Myszka, Waldemar; Nowicki, Marcin; Węgrzyn, Danuta; Drzewiecka, Małgorzata; Kapecka, Kinga; Kozubski, Wojciech (Journal of Medical Science, 2016)
Aim. Ischemia-modified albumin (IMA) is a marker of myocardial ischemia and may be affected by ischemia occurring in other tissues. Migraine has been reported as a risk factor of ischemic stroke or cardiovascular events. Dysfunction of endothelial cells, as well as association with arteriopathies was evidenced in migraine patients. The aim of this study was to evaluate interictal IMA in migraine patients.Material and Methods. Fifty migraineurs aged 38 ± 9 years were included in the study. The control group consisted of 25 healthy volunteers aged 37 ± 8 years. In all subjects neurological examination was carried on, as well as clinimetric evaluation with the use of: MIDAS, MIGSEV, QVM, VAS and VRS. Ischemia-modified albumin was evaluated by means of spectrophotometric method with the use of cobalt chloride. The concentrations of total cholesterol, HDL- and LDL-cholesterol, triglycerides, homocysteine, C-reactive protein and Lp(a) were analyzed with routine spectrophotometric methods.Results. IMA was significantly (P = 0.0108) higher in migraine patients (0.101; 0.00–0.327 O.D.) than in controls (0.00; 0.00–0.102 O.D.; median; interquartile range). Migraineurs with aura have also higher IMA than controls. IMA correlated (rS = 0.383, P = 0.0073) with VAS and with homocysteine concentration (rS = 0.430, P = 0.0026). Multiple regression analysis of IMA and atherosclerosis risk factors showed significant correlation (P = 0.0247) with HDL cholesterol (R = 0.2958) and triglycerides concentrations (R = 0.3285).Conclusions. IMA formation in migraine patients, as a marker of oxidative stress even during interictal period in patients with hyperhomocysteinemia and/or hypertriacylglyceridemia can reflect a milieu of factors which further increases the risk for cardiovascular complications.
Keywords: headache; ischemia-modified albumin; oxidative stress; cerebrovascular diseases